Advances in Wind Energy Conversion Technology - Sathyajith, Mathew; Philip, Geeta Susan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The proposed book provides in-depth discussion on all the major aspects of wind energy conversion technology. Academic and industrial experts share their expertise and experiences in wind energy conversion systems through various chapters grouped in to eight sections. In contrast with other publications in this area, a detailed section on offshore wind farms is included in this volume. Economic and environmental aspects of wind energy coversion are also given due emphasis, along with the recent trends in wind energy engineering. Though a contributory volume, continuity between chapters and sections are maintained throughout the book.
Keywords: Environmental sciences; Climatic changes; Environmental management; Nature Conservation; Environmental protection; Environment; Nature Conservation; Environmental Management; Atmospheric Protection/Air Quality Control/Air Pollution; Climate Change